PERAN MASYARAKAT DAN KUOTA PEREMPUAN DALAM PEMILIHAN UMUM SERENTAK TAHUN 2024 - Wa Ode Nur Iman (Halu Oleo University, 2023)
This paper aims to find out the extent of the role of society and the realization of the women's quota in the implementation of simultaneous general elections which will be held in 2024. Written using a qualitative descriptive method. The data obtained is then analyzed qualitatively with an interactive model and continues continuously until the data is saturated, starting from data collection, data reduction, data presentation and conclusions (miles Huberman and Saldana, 2014). The results of the research show that society as a pillar of democracy plays a very important role in realizing the ideals of democracy, especially holding elections on the principles of Direct, General, Free, Confidential, Honest and Fair as mandated by the Law. Meanwhile, the composition of women who must fulfill the 30% as stipulated in the law, especially as election organizers, still does not fulfill it. So that what must be done for the election in the future is the collaboration of all parties.